Tree root dynamics in montane and sub-alpine mixed forest patches. (28th February 2018) - Wang, Y; Kim, J H; Mao, Z; Ramel, M; Pailler, F; Perez, J; Rey, H; Tron, S; Jourdan, C; Stokes, A
Abstract: Background and Aims: The structure of heterogeneous forests has consequences for their biophysical environment. Variations in the local climate significantly affect tree physiological processes. We hypothesize that forest structure also alters tree root elongation and longevity through temporal and spatial variations in soil temperature and water potential. Methods: We installed rhizotrons in paired vegetation communities of closed forest (tree islands) and open patches (canopy gaps), along a soil temperature gradient (elevations of 1400, 1700 and 2000 m) in a heterogeneous mixed forest. We measured the number of growing tree roots, elongation and mortality every month over 4 years. Key Results: The results showed that the mean daily root elongation rate (RER) was not correlated with soil water potential but was significantly and positively correlated with soil temperature between 0 and 8 °C only. The RER peaked in spring, and a smaller peak was usually observed in the autumn. Root longevity was dependent on altitude and the season in which roots were initiated, and root diameter was a significant factor explaining much of the variability observed. The finest roots usually grew faster and had a higher risk of mortality in gaps than in closed forest. At 2000 m, the finest roots had a higher risk of mortality compared with the lower altitudes. Conclusions: The RER was largely driven by soil temperature and was lower in cold soils. At the treeline, ephemeral fine roots were more numerous, probably in order to compensate for the shorter growing season. Differences in soil climate and root dynamics between gaps and closed forest were marked at 1400 and 1700 m, but not at 2000 m, where canopy cover was more sparse. Therefore, heterogeneous forest structure and situation play a significant role in determining root demography in temperate, montane forests, mostly through impacts on soil temperature.